PEMBUATAN SABUN CUCI TANGAN CAIR BERBASIS BERBAGAI MERK MINYAK ZAITUN DENGAN PENAMBAHAN MINYAK ATSIRI SEREH WANGI (CYMBOPOGON WINTERIANUS JOWITT) - Aisyah, Siti; Raja, Pada Mulia; Purwanto, Heri (Institut Teknologi Sawit Indonesia (ITSI), 2023)
Soap is a product that functions as a cleaner and wash. Hand washing soap in the form of a solution (liquid) is preferred because it looks more attractive and is more practical. Liquid Soap Liquid soap is made through a saponification process using oil and using alkali (KOH). Olive oil contains α-tocopherol (vitamin E) and β-carotene which function as antioxidants. The use of essential oils is good in making perfume, cosmetics, medicines, soap and fragrances, essential oils function as a fixative. The essential oils used are generally patchouli oil, citronella oil, vetiver oil and sandalwood oil. This research aims to make liquid hand washing soap based on various brands of olive oil with the addition of citronella essential oil. The liquid hand washing soap produced is in accordance with SNI, where olive oil-based liquid hand washing soap with brands